Multi-agent based simulation XVI : International Workshop, MABS 2015, Istanbul, Turkey, May 5, 2015, Revised selected papers /: International Workshop, MABS 2015, Istanbul, Turkey, May 5, 2015, Revised selected papers. (2016) - Unknown
No abstract available